TECHNOLOGICAL GAP AND FOREIGN DIRECT INVESTMENT SPILLOVERS IN INDONESIA - Purwono, Rudi; Nur Hamzah, Ibnu; Yasin, Mohammad Zeqi (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
This study investigates the relationship between the technology gap and Foreign Direct Investment (FDI) spillovers in Indonesia. This study employs Medium-Large Manufacturing Survey Data from Statistics Indonesia and employs the standard least-square method to estimate the correlation between the technological gap and industries’ productivity change between 2010 and 2015. This study groups industries based on their technological gap (i.e. the difference between domestic and foreign establishment productivity) into low-technology-gap, medium-technology-gap, and high-technology gap. This study reveals that the effect of the technological gap is higher in the moderate-technology-gap group of industries and that there is a statistically significant positive relationship in the low-technology-gap and high-technology-gap groups. This finding indicates that the technological gap matters for FDI spillovers in Indonesia’s manufacturing and it can explain why there is spillovers from FDI in several industries. This study also reveals that industries with higher level of technological gap tend to have higher variation in productivity change, thus it can explain the difference between industries absorptive capacity. Therefore, promoting FDI inflows in the country also fosters domestic firms’ productivity growth especially FDI with relatively higher technology than domestic firms. These findings also recommend that the government support domestic firms’ absorptive capacity after promoting FDI inflow into the country.